The short-term response of the Hispanic noncitizen population to anti-illegal immigration legislation The case of Arizona SB 1070 - Gonzalo E. Sánchez (Journal of Economics, Finance and Administrative Science, 2017)
Purpose – This paper aims to examine the short-term effect of the Arizona Immigration Law of 2010 (SB 1070) on the noncitizen Hispanic state population. Design/methodology/approach – To get a consistent estimate of this effect, a synthetic control method has been used to calculate a suitable counterfactual. Findings – Results indicate that this bill produced a statistically significant short-term reduction in the proportion of noncitizen Hispanics in Arizona between 10 and 15 per cent. However, the evidence suggests that this effect vanishes after a few months. Originality/value – These findings are consistent with previous evidence of the high mobility of the undocumented population in the US, and contribute to the understanding of the effects of federal and statelevel immigration legislation.
Keywords: J61; J68; 330; Hispanic population; Illegal immigration; Synthetic control